Control of tissue‐localized immune responses by human regulatory T cells. Issue 2 (8th December 2014) - Pesenacker, Anne M.; Broady, Raewyn; Levings, Megan K.
<x xml:space="preserve">Abstract</x> Treg cells control immune responses to self and nonharmful foreign antigens. Emerging data from animal models indicate that Treg cells function in both secondary lymphoid organs and tissues, and that these different microenvironments may contain specialized subsets of Treg cells with distinct mechanisms of action. The design of therapies for the restoration of tissue‐localized immune homeostasis is dependent upon understanding how local immune responses are influenced by Treg cells in health versus disease. Here we review the current state of knowledge about human Treg cells in four locations: the skin, lung, intestine, and joint. Despite the distinct biology of these tissues, there are commonalities in the biology of their resident Treg cells, including phenotypic and functional differences from circulating Treg cells, and the presence of cytokine‐producing (e.g. IL‐17+) FOXP3+ cells. We also highlight the challenges to studying tissue Treg cells in humans, and opportunities to use new technologies for the detailed analysis of Treg cells at the single‐cell level. As emerging biological therapies are increasingly targeted toward tissue‐specific effects, it is critical to understand their potential impact on local immune regulation.